Diagnostic Instruments of Four-Tier Test Work and Energy (FORTUNE) to Identify The Level of Students’ Conceptions - Aripiani, Shabrina Khairunnisa; Samsudin, Achmad; Kaniawati, Ida; Novia, Hera; Aminudin, Adam Hadiana; Sutrisno, Asep Dedy; Coştu, Bayram (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This study aims to develop and examine students' conceptions of Work and Energy in relation to the Indonesian Capital City in East Kalimantan, using the Four-Tier Test of Work and Energy (FORTUNE) Open-Ended. The 4D methodology was followed, involving defining, designing, developing, and disseminating the research. The FORTUNE test, comprising 13 questions, was administered to 70 tenth-grade students (44 girls and 26 boys) aged 15 to 16. Rasch analysis was applied to categorize student responses into seven distinct categories: Sound Understanding (SU), Partial Positive (PP), Partial Neutral (P0), Partial Negative (PN), Misconception (MC), No Understanding (NU), and No Coding (NC). The results revealed that FORTUNE effectively diagnosed students' conceptions, with 61% of responses falling into the Misconception (MC) category, while only 3% were classified as Partial Positive (PP). Notably, students displayed misconceptions in questions of moderate difficulty, as indicated by Rasch analysis. In conclusion, this study successfully developed and implemented the FORTUNE Open-Ended test to assess students' conceptions of Work and Energy in the context of the Indonesian Capital City in East Kalimantan. The findings highlight the prevalence of misconceptions among students, particularly in questions of moderate difficulty. Addressing and rectifying these misconceptions require targeted instructional strategies to foster a deeper and more accurate understanding of the topic. Future research should explore the effectiveness of intervention programs aimed at enhancing students' conceptual understanding of Work and Energy.